2016
DOI: 10.1016/j.neurobiolaging.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

The Ames dwarf mutation attenuates Alzheimer's disease phenotype of APP/PS1 mice

Abstract: APP/PS1 double transgenic mice expressing human mutant amyloid precursor protein (APP) and presenilin-1 (PS-1) demonstrate robust brain Aβ peptide containing plaque deposition, increased markers of oxidative stress, behavioral dysfunction, and proinflammatory gliosis. On the other hand, lack of growth hormone, prolactin, and thyroid-stimulating hormone due to a recessive mutation in the Prop 1 gene (Prop1df) in Ames dwarf mice results in a phenotype characterized by potentiated anti-oxidant mechanisms, improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 105 publications
0
15
0
Order By: Relevance
“…Previously, we demonstrated higher levels of IGF-1 in the parietal cortex but not the hippocampus of AβPP/PS1 mice at 6 months of age compared to WT mice (Puig et al, 2016 ). The present data also revealed no significant differences in IGF-1 levels between these two genotypes in the temporal cortices of 9–10-month-old mice before or after the drug exposure ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previously, we demonstrated higher levels of IGF-1 in the parietal cortex but not the hippocampus of AβPP/PS1 mice at 6 months of age compared to WT mice (Puig et al, 2016 ). The present data also revealed no significant differences in IGF-1 levels between these two genotypes in the temporal cortices of 9–10-month-old mice before or after the drug exposure ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 70%
“…Based on the potential role of IGF-1R suppression against AD development and according to our previous data which reported diminished gliosis and Aβ burden in the df/df/AβPP/PS1 transgenic mice which express low levels of brain IGF-1 (Puig et al, 2016 ), we hypothesized that applying a short-term pharmaceutical intervention might attenuate disease presentation. To test this idea, we intraperitoneally injected PPP into the AβPP/PS1 mouse line and wild type littermate controls for a week to investigate changes in gliosis and plaque deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both male and female long-lived Ames dwarf mice, which are characterized by circulating GH and IGF-1 deficiency, have normal cognitive function that is better maintained with age, based on performance in memory tests, when compared to age-matched controls (Kinney et al 2001b). Although there is some evidence that local IGF-1 production in these animals is enhanced (Sun, et al 2005), suggesting that autocrine IGF-1 production may be an important contributor to cognitive health, subsequent studies did not confirm these results, finding lower IGF-1 levels in the cortex and hippocampus of these mice compared to wild-type controls(Puig, et al 2016). On the contrary, liver-specific IGF-1 deficient (LID) mice, which have an approximately 70% reduction in systemic IGF-1 levels, manifest early hippocampal-dependent cognitive deficits (Trejo, et al 2007), including a reduction in spatial learning and memory (assessed by Water Maze) ((Svensson, et al 2006; Trejo et al 2007) despite maintained autocrine IGF-1 production.…”
Section: Igf-1 and Cognitionmentioning
confidence: 97%
“…A number of rodent studies have suggested that relative IGF-1 deficiency and/or reduced IGF-1 signaling confers protection against progression of AD pathology. For instance, Ames Dwarf mice expressing human mutant amyloid precursor protein (APP) and presenillin-1 (PS1) demonstrated lower brain IGF-1 levels and reduced amyloid plaque deposition than controls (Puig et al 2016). Likewise, heterozygous deletion of the IGF1R in a similar AD model protected from AD-like symptoms, neuroinflammation, neuronal loss, and delayed proteotoxicity in 12-13 month old mice compared to age-matched controls (Cohen, et al 2009).…”
Section: Igf-1 and Alzheimer’s Diseasementioning
confidence: 99%
“…Another fact implicating the PG as a source of such regulation is the above-mentioned anti-aging effect and extension of the lifespan caused by hypophysectomy in adult animals [ 55 , 56 ]. In addition, it was previously demonstrated that dwarf mice have longer lifespans and that df/df/APP/PS1 hybrid mice, a cross between dwarf mice and double transgenic mice expressing human mutant amyloid precursor protein (APP) and presenilin-1 (PS1), have reduced Aβ plaque deposition and less Aβ 1-40 and Aβ 1-42 concentrations in the brain [ 92 ]. Notably, the age effect on plasma concentrations of PG-enriched miRNAs (e.g., miR-127-5p, miR-154, miR-369, miR-381, miR-410, and miR-411) is 10-20 times lower in dwarf mice than in normal controls [ 93 ].…”
Section: Introductionmentioning
confidence: 99%